REFLEXÕES ÉTICAS SOBRE CRISTIANISMO E ABORTO NO BRASIL: considerações acerca da discriminalização (Caderno Espaço Feminino, 2016)
ResumoEste artigo tem o objetivo de propor uma reflexão sobre o aborto relacionando os argumentos morais do cristianismo ao processo de criminalização do mesmo, promovendo uma discussão que contribua para uma melhor informação e consequente reflexão da comunidade acadêmica e da sociedade brasileira acerca do tema. A metodologia utilizada na elaboração da pesquisa que resultou neste artigo é de cunho bibliográfico buscando investigar as bases morais que subsidiam a criminalização das mulheres que abortam no Brasil. No processo de conclusão do trabalho de pesquisa, foi possível perceber que os argumentos apresentados nos textos investigados, estavam intrinsecamente relacionados a valores da moral cristã nos moldes como são interpretados pela igreja e disseminado na sociedade atingindo inclusive seu aparato legal que criminaliza a mulher que aborta.Palavras Chave: Aborto. Cristianismo. Ética. Descriminalização.ETHICAL REFLECTIONS ON CHRISTIANITY AND ABORTION IN BRAZIL: considerations about decriminalizingAbstractThe objective of this article is to offer a reflection on the abortion issue which intends to relate the moral arguments of Christianity to the the abortion criminalization process, in order to promote a discussion that will contribute to better information, and subsequent reflection from both the academic community and Brazilian society, about the decriminalization of abortion in Brazil. The methodology used in preparing the research that resulted in this article was of a bibliographic nature which sought to investigate the moral foundations which promote the criminalization of women who have abortions in Brazil. At the conclusion of the research, it was observed that the arguments presented in the investigated texts were intrinsically related to Christian moral values, in the manner that they have been interpreted by the Church and disseminated in society, reaching even the societal legal apparatus that criminalizes woman who have abortions.Keywords: Abortion. Christianity. Ethics. Decriminalization.